Exacerbation risk in severe asthma is stratified by inflammatory phenotype using longitudinal measures of sputum eosinophils. Issue 10 (27th June 2016) - Walsh, C. J.; Zaihra, T.; Benedetti, A.; Fugère, C.; Olivenstein, R.; Lemière, C.; Hamid, Q.; Martin, J. G.
Summary: Background: Airway inflammatory phenotyping is increasingly applied to subjects with asthma. However, its relationship to clinical outcomes in difficult asthma is incompletely elucidated. Objective: The goal of our study was to determine the relationship between exacerbation rates and phenotypes of difficult asthma based on the longitudinal measures of sputum eosinophils and neutrophils. Methods: Subjects in the longitudinal observational study from two tertiary care centres that completed 1 year of observation and provided at least three sputum samples were classified by inflammatory phenotypes using previously established thresholds. Kaplan–Meier curves and univariable and multivariable Cox proportional hazard models were used to determine the association between inflammatory phenotypes and exacerbation rate. Results: During the study, 115 exacerbations occurred in 73 severe asthmatic subjects. Subjects with the persistently eosinophilic phenotype had a significantly shorter time to first exacerbation and greater risk of exacerbation over a 1‐year period than those with the non‐eosinophilic phenotype based on the univariable and multivariable Cox proportional hazard model (hazard ratio [HR], 3.24; 95% confidence interval [CI], 1.35–7.72; adjusted HR, 3.90; 95% CI, 1.34–11.36). No significant differences in time to first exacerbation or exacerbation risk over a 1‐year period were observed among the neutrophilic phenotypes. Conclusions: The persistent eosinophilic phenotype is associated with increased exacerbation risk compared with the non‐eosinophilic phenotype in severe asthma. No differences in time to first exacerbation or exacerbation risk over a 1‐year period were detected among neutrophilic phenotypes.